DINAMIKA PERILAKU MENOLONG BYSTANDER PADA KORBAN BULLYING DI SEKOLAH - Patria Jati Kusuma; Wanodya Kusumastuti (Program Studi S1 Psikologi, 2020)
School is a place to construct the character and personality of student. In the current status qou, the teaching and learning process in the school is often misslead with the development of its student, one of the behavior is bullying. The case of bullying is not only involved the perpetrator and victim but also the bystander. This 3rd actor can determine whether the act of bullying can be dismissed or not. This study aimed to know the role of bystander while the act of bullying occurs. The purpose of this study was to analyze and discuss the patterns of bystander's helping behavior to the victims of intimidation. The method utilized in this study was a qualitative design with open ended questioner. The data analysis of this study was using the descriptive analysis. The stages consist of research analyze, library research, data collection which used to analyze the data by describing or analyzing the collected data, determining the categories, and to draw the conclusions. The participants of this study were 150 students of Surakarta X Vocational High School who has the similar characteristics as observers. The results of this study found that the actions taken by bystander when encountering bullying in schools were reporting to the teachers (42.67%), suggesting the victims to avoid the perpetrators (30%), separating the actors (16%), and helping victim to fight offender (11.33%).